Formulation and Characterization of SNEDDS of Dayak Onion Extract with Comparative Variations of Surfactants, Co-Surfactants, and Palm Oil - Annisa, Rahmi; Firdausy, Alif Firman; Alawiyah, Ihda Mahila; Reformasiska, Farianda (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v1i0.1455, 2021)
Self-Nanoemulsifying Drug Delivery System (SNEDDS) is a thermodynamically stable drug administration unit with the capacity to increase the solubility of active pharmaceutical ingredients (API) and bioavailability. In addition, dayak onion extract is an active ingredient developed to increase the effectiveness of therapy. The aims to formulate, characterize, and investigate stability. Moreover, the HLB approach was used to formulate SNEDDS from dayak onion extract, with a component ratio of palm oil, a combination of surfactants (hydrophilic Tween 80, Tween 20) and lipophilic (Span 20 and Transcutol) and PEG 400 as co-surfactants. A total of sixty formulas were used, with an HLB range of 11-15 and a ratio of 1:8:1, 1:7:2, and 2:7:1, followed by evaluating product characteristics. Furthermore, two formulas were selected, including F13 (HLB 13) and F34 (HLB 14), at ratios 1:8:1 and 1:7:2. The results showed particle size ranging from 10-200 nm, percent transmittance of <90%, while the viscosity and pH values were stable at various dilutions. The evaluation for thermodynamics indicates an unstable preparation. Therefore, the SNEDDS formula of dayak onion extract using long-chain triglycerides (palm oil) was ineffective.